On the analysis of isometric immersions of Riemannian manifolds - Giron, T (2020)
This thesis is a study of problems related to isometric immersions of Riemannian manifolds in Euclidean space. We address three main questions: the weak continuity of geometric invariants along sequences of immersions of Riemannian manifolds; the construction of isometric immersions by weak compactness methods; and the validity and regularity of the Gauss equation.